2019
DOI: 10.1002/lary.28187
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nationwide readmissions after parotidectomy

Abstract: Objectives: To evaluate the incidence, causes, risk factors, and costs associated with 30-day readmissions in parotidectomy patients utilizing the Nationwide Readmissions Database (NRD).Study Design: Retrospective cohort study. Methods: We examined the NRD for patients who underwent parotidectomy between 2010 and 2014. Rates, causes, and costs of 30-day readmissions were determined. Multivariate logistic regression was used to identify risk factors for readmission.Results: Among 15,102 included patients, 594 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Additionally, the readmission rate was 1.47% in the outpatient group and 2.01% in the inpatient group (P = .71), both lower than the national reported rate of 3.9%. 26 Coniglio et al 18 have previously reported that intraoperative drain usage in the parotidectomy procedure does not have a significant impact on postoperative complications. This is concordant with our research, where we found no significant difference in complication rate by drain status.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the readmission rate was 1.47% in the outpatient group and 2.01% in the inpatient group (P = .71), both lower than the national reported rate of 3.9%. 26 Coniglio et al 18 have previously reported that intraoperative drain usage in the parotidectomy procedure does not have a significant impact on postoperative complications. This is concordant with our research, where we found no significant difference in complication rate by drain status.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the readmission rates gathered from National Surgical Quality Improvement Program appear to be lower than the 4 per cent readmission rate calculated from the nationwide readmission database. 32 This discordance of values may be attributed to the fact that the National Surgical Quality Improvement Program only considers readmissions within 30 days post-operatively whereas the nationwide readmission database accounts for 30 days after discharge. Thus, if a patient had a prolonged hospital stay, American College of Surgeons National Surgical Quality Improvement Program may have underestimated the readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent US nationwide study has found that a LOS [? ]2 days was an independent risk factor for readmission within 30 days following parotidectomy [ 25 ]. Considering that the cost of a hospitalization day is USD [?…”
Section: Discussionmentioning
confidence: 99%